Critical religion and critical research on religion: Religion and politics as modern fictions - Fitzgerald, Timothy (Critical research on religion, 2015)
The purpose of this response piece is to summarize what is meant by "critical religion" as a contribution to the ongoing debates within the discipline, and specifically in relation to critical research on religion.